PENGARUH PROMOSI KESEHATAN DENGAN METODE CERAMAH TENTANG KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG SEKS PRANIKAH - novia artika; Riska Ratnawati (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Reproductive health is a healthy condition with reproductive systems, functions, and processes possessed by adolescents. Lack of knowledge and attitudes about reproductive health affect premarital sexual behavior. One effort to increase knowledge about premarital sex is to provide health promotion. This study aims to determine the effect of health promotion with the lecture method on reproductive health to the knowledge and attitudes of adolescents about premarital sex in "X" State High School in Ngawi Regency. This type of research is an experimental study using (One Group Pretest and Posttest Design). Measuring instruments in this study used a questionnaire with a non-parametric analysis test with the Wilcoxon Test. The results of the Wilcoxon Test found that the Asymp.Sig (2-tailed) value = 0,000 with a significance level of 0.05. The testing criteria are that H0 is rejected if Asymp.Sig <0.05. Because the Asymp.Sig results of knowledge and attitudes smaller than 0.05 means H0 is rejected so there is an influence of health promotion by lecture methods about premarital sexual and reproductive health on knowledge and attitudes to students. The conclusion of this study is that health promotion with a lecture method on reproductive health has an effect on increasing the knowledge and attitudes of adolescents about premarital sex in SMA "X" in Ngawi Regency.Keywords: Health Promotion, Reproductive Health, Premarital Sexuality, Knowledge, Attitude.